Sistem Kontrol All In One Top Filter Pada Akuarium Menggunakan Arduino Uno - Muhammad Kurniawan; Ade Zulkarnain; Adidtya Perdana (Universitas Harapan Medan, 2021)
In terms of maintaining goldfish there are several factors that must be considered such as water temperature, pH levels and feeding that must be considered. Traditionally, checking the condition of aquarium water is carried out routinely by paying attention to water color and odor, traditional methods still lack accuracy and time efficiency. In the handling of feeding, it is classified based on the time of feeding for goldfish. Therefore, an automation system is needed in this case to overcome the accuracy of checking and feeding routines. By utilizing a microcontroller system that is connected to a temperature sensor, pH sensor, servo motor, RTC and Fan. The pH sensor detects the pH of the aquarium water when the aquarium water is low the pH lowering servo activates immediately. If the pH is detected as high, the pH lowering servo will be active. The temperature sensor detects the aquarium water temperature, if the aquarium temperature is more than 30 C then the Fan will turn on, and when the temperature is back to normal, the Fan will turn off automatically. The RTC reads the feeding time on the Arduino Uno program, when it enters the feeding schedule, the feed servo will move 180? to pour the feed